The Journal of Organizational Computing and Electronic Commerce: An Analysis of Its Impact on the Information Systems Field in the 21st Century. Issue 2 (3rd April 2021) - French, Aaron M.; Storey, Veda C.
ABSTRACT: The Journal of Organizational Computing and Electronic Commerce (JOCEC) is entering its 31st year since its inception. This paper examines the history and impact of JOCEC and highlights its significant contributions. We analyze the impact of the journal's research articles using emerging metrics, such as CrossRef, Google Citations, and Altmetrics. The results show the relationship between these new metrics and views and citation counts. We also identify the most influential publications, authors, and topics over the past 30 years.